(untitled) (Gestionar: revista de empresa y gobierno, 2026)
Currently, events that challenge the stability of professional football clubs are an everyday matter; environments are more dynamic and uncertain, causing significant transformations in their management and operation. in response, these organizations rely on various administrative methods that allow them to adapt and better address the challenges presented by the environment, one of which is benchmarking. the objective of this essay was to reflect on this organizational method for managing a club oriented toward learning and improving its performance both on and off the field. methodologically, it was based on a documentary study, using hermeneutics to analyze texts related to how this administrative knowledge is a valuable method for managing and operating clubs in uncertain and challenging environments. to this end, the concept and its characteristics were defined, reflecting on how this knowledge is being applied in such organizations. it concludes that the proper use of this organizational methodology is an effective, efficient, and successful contribution to achieving sporting and economic objectives.